Effect of nanosilver on cortisol release and morphometrics in rainbow trout (Oncorhynchus mykiss). (11th January 2017) - Murray, Laura; Rennie, Michael D.; Enders, Eva C.; Pleskach, Kerri; Martin, Jonathan D.
Abstract: Nanosilver (nAg) is a nanoparticle commonly incorporated into consumer products for its antimicrobial properties that has been detected in aquatic environments. Toxic effects of nAg on fish have been observed, and nAg may induce a stress response in fish in the form of increased blood plasma cortisol. Effects of nAg exposure on rainbow trout ( Oncorhynchus mykiss ) were investigated over a 28‐d period using blood plasma cortisol concentrations as an indicator of stress. Several morphometric measures (growth, Fulton's condition factor, and hepatosomatic index [HSI]) were also taken during the experiment to investigate potential whole‐body effects of exposure, and concentrations of nAg in fish muscle tissue were measured. Fish were exposed to environmentally relevant (average 0.28 μg/L) and higher (average 47.60 μg/L) exposure concentrations of nAg. The results showed a significant increase in blood plasma cortisol for both exposure treatments. A significant effect on HSI by treatment dependent on exposure time was also observed, although no obvious trend was detected, whereas other morphometric measures were not affected by nAg exposure. In addition, Ag was detected in fish muscle tissue. The results indicate that although nAg did engage the stress response in fish, it did not affect growth or condition under the experimental conditions and time frame investigated. Environ Toxicol Chem 2017;36:1606–1613. © 2016 SETAC